Sigma-1 receptor regulates mitophagy in dopaminergic neurons and contributes to dopaminergic protection. (15th September 2021) - Wang, Mingmei; Wan, Chunlei; He, Tao; Han, Chaojun; Zhu, Kailian; Waddington, John L.; Zhen, Xuechu
Abstract: Mitochondria are essential for neuronal survival and function, and mitochondrial dysfunction plays a critical role in the pathological development of Parkinson's disease (PD). Mitochondrial quality control is known to contribute to the survival of dopaminergic (DA) neurons, with mitophagy being a key regulator of the quality control system. In this study, we show that mitophagy is impaired in the substantia nigra pars compacta (SNc) of the 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-induced mouse model of PD. Treatment with the sigma-1 receptor (Sig 1R) agonist 2-morpholin-4-ylethyl 1-phenylcyclohexane-1-carboxylate (PRE-084) reduced loss of DA neurons, restored motor ability and MPTP-induced damage to mitophagy activity in the SNc of PD-like mice. Additionally, knockdown of Sig 1R in SH-SY5Y DA cells inhibited mitophagy and enhanced 1-methyl-4-phenylpyridinium ion (MPP + ) neurotoxicity, whereas application of the Sig 1R selective agonist SKF10047 promoted clearance of damaged mitochondria. Moreover, knockdown of Sig 1R in SH-SY5Y cells resulted in decreased levels of p-ULK1 (Unc-51 Like Autophagy Activating Kinase 1) (Ser 555 ), p-TBK1 (TANK Binding Kinase 1) (Ser 172 ), p-ubiquitin (Ub) (Ser 65 ), Parkin recruitment, and stabilization of PTEN-induced putative kinase 1 (PINK1) in mitochondria. The present data provide the first evidence for potential roles of PINK1/Parkin in Sig 1R-modulated mitophagy in DA neurons. Highlights: Mitophagy is impaired in the substantia nigra of MPTP-induced Parkinsonism mice. Sig 1R dysfunction induces disturbance in depolarized mitochondria degradation under CCCP treatment in dopaminergic cells. Activation of Sig1R stimulates markers of mitophagy, likely through PINK1/Parkin pathway in dopaminergic cells and attenuates MPTP-induced motor disability.